Development of Augmented Reality (AR) Based Pop-Up Book Interactive Learning Media to Improve Class V Science Learning Outcomes - Sasa Mutmainah; Sri Sami Asih (Jurnal Penelitian Pendidikan IPA, 2026)
Science learning in elementary schools still faces various obstacles and limitations, particularly in the use of learning media that lacks interactiveness and the inability to concretely visualize abstract material. This research, conducted through R&D, aims to test the feasibility, practicality, and effectiveness of the interactive Pop-Up Book learning media based on Augmented Reality (AR). The media's feasibility was demonstrated by validation results from media experts with a percentage of 78.18% and material experts with a percentage of 84.61%. Based on the results of the pretest and posttest, it shows that the Pop-Up Book media based on augmented reality (AR) is effective in improving student learning outcomes with an increase in the average pretest and posttest scores indicated by the N-Gain test results obtaining a value of 0.77 with a high category. Practicality is shown from the results of the teacher response questionnaire which obtained a percentage of 92.50% with a very good category, while student responses in small-scale trials obtained a percentage of 83% with a very good category and large-scale trials of 80.40% with very good. The data shows that the interactive learning media Pop-Up Book based on augmented reality (AR) is practical, feasible, and effective to be used to improve the learning outcomes of science students of grade V SDN Sadeng 01 Semarang.